COMPREHENSION OF MARKETING RESEARCH TEXTS AMONG SOUTH AFRICAN STUDENTS: AN INVESTIGATION - Berndt, Adele; Petzer, Daniel J; Wayland, Jane P (South African Journal of Higher Education, 2016)
Reading is a skill people require to successfully operate in all spheres of life. Mastering this skill is even more critical when pursuing academic studies. This particular study investigated the reading comprehension of final year undergraduate marketing students at a South African university relating to their comprehension of marketing research texts. Two measurement instruments were used to test reading comprehension. One instrument contained two passages from the respondents’ prescribed marketing research text and the other two passages from a comparative international text. Following the Cloze procedure, every 9th word was removed from the passages and respondents were subsequently required to complete the non-subject related words in one of the instruments fielded on a random basis. The results indicate that the majority of respondents exhibit a reading comprehension that is at the frustration reading level. A further evaluation that allowed for synonyms (SEMAC) to be included, did not impact meaningfully on the classification of respondents. Significant differences in reading comprehension could also not be uncovered based upon gender and home language. The results furthermore present challenges for all those involved in higher education, more specifically impacting on textbook choice as well as assessment and performance practices.